1991
DOI: 10.1203/00006450-199111000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucose Infusion on Leucine Transamination and Oxidation in the Ovine Fetus

Abstract: ABSTRACT. During fasting of the ewe, the rate of amino acid oxidation by the ovine fetus increases substantially. We hypothesized that the increase in amino acid oxidation derived mainly from reduced protein synthesis. We further hypothesized that fetal glucose supplementation would result in diminished amino acid oxidation. To test these hypotheses, nine ovine fetuses were infused with [15N,1-'3C]leucine to determine the rates of leucine appearance and disposal. Simultaneously, the fetal uptake of leucine was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 12 publications
4
12
1
Order By: Relevance
“…Indeed, fetal amino acid nitrogen uptake significantly increases during hypoglycemic hyperinsulinemia (31 ). Estimates ofnormal fetal leucine uptake have ranged from 3.7 to 4.7 Atm/kg per min ( 12,14,27,29,40), values that agree with the control measurements of this study. The contribution of a-ketoisocaproate to the uptake of leucine carbon skeleton has been less well studied.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Indeed, fetal amino acid nitrogen uptake significantly increases during hypoglycemic hyperinsulinemia (31 ). Estimates ofnormal fetal leucine uptake have ranged from 3.7 to 4.7 Atm/kg per min ( 12,14,27,29,40), values that agree with the control measurements of this study. The contribution of a-ketoisocaproate to the uptake of leucine carbon skeleton has been less well studied.…”
Section: Discussionsupporting
confidence: 79%
“…Second, any effects of somatostatin (either primary or secondary) on fetal protein metabolism should be equally present during both control and experimental conditions. Estimates of fetal leucine disposal using the reciprocal pool model (i.e., calculated from a-ketoisocaproate specific activity) have ranged from 10 to 14 Amol/min per kg ( 12,14,27,29), which are in excellent agreement with our control measurements. We found that fetal leucine disposal was unaffected by changing insulin concentrations from low to normal.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Ovine premature fetuses showed reamination rates approximately twice the rate of leucine appearance from protein breakdown (23,24). This is in contrast with our results, where reamination rates are only one third of the proteolysis rates.…”
Section: Discussioncontrasting
confidence: 57%
“…In a model of heat stress-induced IUGR, maternal-placental leucine flux is reduced and leucine is subsequently redirected toward fetal metabolism via decreased placental utilization and decreased leucine flux from the fetus to the placenta (36). Maternal starvation of pregnant ewes elevates fetal leucine oxidation, which is inversely correlated with fetal glucose concentration (7,9). Although both of these studies provide important physiologic insight, neither approach the organ-specific molecular biology behind their findings.…”
Section: Liver and Muscle Bckad In Iugr Fetal Ratsmentioning
confidence: 99%